Audit Sistem Informasi Absensi Fingerprint Menggunakan COBIT 5 - Matius Agustinus; Eva Zuraidah (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
An information system audit is carried out to ensure that the system used for attendance in agencies is running well, using the Cobit 5 framework located at UPP PKB Samsat Jakarta Timur, because it is not yet known to what extent the capability level of the attendance system is, is there monitoring, evaluation in managing operations in the attendance system, and there is no evaluation of the level of security and performance of the attendance system. The purpose of this study is to determine the extent to which the attendance system monitors and evaluates environmental controls, assessments, and restoration of independent certainty, evaluates the level of security and performance of information systems in this case attendance. The method used is using the domain from COBIT 5, there are 3 domains used in this study, namely DSS01 Managed Operations, DSS05 Managed Security Service and MEA01 Monitor, Evaluate and Assess Performance and Conformance. By making 85 questions and distributing them through a questionnaire to 13 respondents, the results obtained were that the MEA01 domain got a maturity level value of 2.90 with a Fully achievement score, got an Established Process level capability, and a GAP value of -0.10 from target level 3. DSS01 got a maturity level value 2.03 with a Fully achievement value, getting Managed Process level capability, and a GAP value of -0.97 from target level 3, only slightly above the expected target. For the lowest domain, DSS05 gets a maturity level value of 1.44 with a Fully achievement score getting a Performed Process level capability, and a GAP value of -1.56 from target level 3